Strengthening The Capacity Of Customary Institutions Of The Kampong Consultancy Agency (BPK) Through Training For The Preparation Of Qanun For Stunting Prevention And Management In The City Of Subulussalam - Nih Farisni, Teungku; Fitriani, Fitriani; Yarmaliza, Yarmaliza; Putra, Onetusfifsi (SEAN Institute, 2023)
The achievements of this study was (1) increasing BPK and Gampong Government's understanding of the formation of gampong regulations; and (2) stipulation of draft qanun/regulation on Prevention and Reduction of Stunting as a legal basis for the government of Bukit Alim Village, Longkip District, Subulussalam City. (3) To Increase community involvement and awareness in stunting prevention and eradication initiatives in gampongs. The way to achieve this goal was training and assistance in the formation of qanuns.